Kontribusi Trait Kepribadian dan Prestasi Belajar pada Mahasiswa Fakultas Psikologi Angkatan 2014 di Universitas â€˜Xâ€™ Bandung - Priska Analya; Meilani Rohinsa (Universitas Kristen Maranatha, 2017)
The Aim of this study is with Â to acquire the contribution of Personality Trait and academic Achievement on sitxth grade students of psychology faculty in â€œXâ€ University-Bandung. The variable in this research was measured by using The NEO-Personality-Revised questionnaire that had translated by the researcher, based on Costa and McCrae (1992). The questionnaire consist of Â 120 items self-report. The result of validity test is in the midst of 0,322 - 0,598, and the reliability score for Neuroticism is 0,65, Aggreableness is 0,78, Extraversion is 0,67, conscientiousness isÂ 0,61, andÂ Openness is 0,83. Classical Assumption for regression using Multicolinearity diagnostic and Glejser. Using the purposive sampling as the sampling technique, the researcher obtained 170 students as respondents in this research. The results of this study showed that regression model canâ€™t be used to predict Trait Personality and Academic Achievement. Big Five personality trait donâ€™t have significant influence with Academic Achievement. Big Five Personality traitâ€™s contribution score to Academic Achievement are 2,7%. Suggestion for the next study, should consider the variation of Academic Achievement, and the proporsion of age and gender. The other Suggestion is to assess contribution of another factors such as time management, anxiety, and self efficacy with Academic Achievement